2019
DOI: 10.1177/1120672119877139
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes and efficacy of pars plana vitrectomy-hyaloidotomy-zonulectomy-iridotomy in malignant glaucoma

Abstract: Aim: To study the treatment outcomes and efficacy of pars plana vitrectomy-hyaloidotomy-zonulectomy-iridotomy in malignant glaucoma. Method: A retrospective case series study of patients treated for malignant glaucoma between 2005 and 2017. The treatment included medical management as first-line in the form of cycloplegic with anti-glaucoma medications (AGM) or pars plana vitrectomy-hyaloidotomy-zonulectomy-iridotomy as second-line therapy. The resolution was defined as ‘deepening of central anterior chamber’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…On day 14, after the diagnosis of malignant glaucoma, a 23-gauge complete PPV with irido-zonulo-hyaloidotomy was performed on our patient. Similar procedures were described and the majority of patients observed no or very low recurrence throughout the follow-ups [ 2 , 4 , 5 ]. During the post-operative period, the IOP was maintained at mid-teens without IOP-lowering eye drops.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…On day 14, after the diagnosis of malignant glaucoma, a 23-gauge complete PPV with irido-zonulo-hyaloidotomy was performed on our patient. Similar procedures were described and the majority of patients observed no or very low recurrence throughout the follow-ups [ 2 , 4 , 5 ]. During the post-operative period, the IOP was maintained at mid-teens without IOP-lowering eye drops.…”
Section: Discussionmentioning
confidence: 91%
“…Its incidence ranges from 0.6% to 4% in eyes treated surgically for angle-closure glaucoma, with a higher prevalence after penetrating glaucoma surgeries [ 6 ]. Pseudophakia post-cataract surgery has been previously included as one of the possible triggering factors [ 4 , 6 ]. It can be classified into: (i) classic malignant glaucoma, which happens after incisional surgery in patients with primary angle-closure glaucoma; (ii) non-phakic malignant glaucoma, which occurs in patients who have had cataract-removal surgery, which is seen in our case; and (iii) other malignant glaucoma syndromes, which have sporadic occurrence and may be associated with laser, miotic agents, and trabeculectomy bleb needling [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If both medical and laser treatment fail, pars plana vitrectomy is thought to prevent aqueous humour from accumulating in the vitreous cavity and the hyaloido‐zonula‐iridectomy to ensure the communication between the anterior chamber and the vitreous cavity. A few studies have combined the vitrectomy and HZI with the removal of the lens and implantation of IOL if the patients were phakic (Debrouwere et al 2012; Dervenis, Mikropoulou & Dervenis 2017; Tang, Du & Li 2018; Raj et al 2019). We cannot determine whether vitrectomy with HZI combined with phacoemulsification gives a better result than vitrectomy with HZI alone.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies did not consider cases treated with additional surgeries as relapses (Al Bin Ali et al 2017; Krėpštė, Žemaitienė & Miliauskas 2018). Studies using anterior, core or partial PPV with HZI had variable relapse rates (Bitrian & Caprioli 2010; Koukkoulli & Rahman 2013; Rękas, Krix‐Jachym & Zarnowski 2015; A Khan 2016; He et al 2016; Balekudaru et al 2017; Rani et al 2018; Tang, Du & Li 2018; Patel 2020; Raj et al 2019). One study based on one eye reported relapse that resolved with slit‐lamp needling (Mardelli & Mardelli 2018).…”
Section: Methodsmentioning
confidence: 99%